(untitled) (Research, Society and Development, 2022)
This study aimed to analyse possible training needs of higher education teachers (HE) of Accounting Sciences, for the use of active methodologies with game elements as tool didactic-pedagogical. This is a qualitative research, whose data were obtained through a questionnaire applied to a group of professors working at a University located in the North region of Paraná. For data analysis, the precepts of Discursive Text Analysis (ATD) were used, which made it possible to infer that the researched sample recognizes its training needs in order to better equip itself so that its teaching practice is adequate to the demands of the accounting profession. They showed interest in participating in continuing pedagogical training courses that address the concepts of gamification and the possible applications in the scope of the subjects they teach, considering the possibilities and benefits brought to the teaching and learning process with the application of this strategy.